CircRNAs in colorectal cancer: potential roles, clinical applications, and natural product-based regulation - Yang, Jingjing; Fan, Qiqi; Wang, Yiyun; Liu, Yuanyue; Xu, Xiaoning; Liang, Yeqi; Xie, Jiakang; Li, Jiajie; Ai, Fengting; Cao, Yong; Yu, Shangzhen; Liu, Jinman (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is one of the leading causes of cancer-related mortality worldwide. In recent years, circular RNAs (circRNAs), a novel class of non-coding RNA molecules, have emerged as a research focus due to their unique stability and functional roles. CircRNAs regulate tumor-related signaling pathways through interactions with microRNAs (miRNAs) and proteins, playing key roles in tumorigenesis, progression, invasion, metastasis, and chemoresistance. This review summarizes the role of circRNAs in CRC, particularly their mechanisms in cell proliferation, migration, apoptosis, tumor microenvironment (TME) remodeling, and immune evasion. Aberrant expression of circRNAs holds great potential as diagnostic and prognostic biomarkers as well as therapeutic targets for CRC. Additionally, natural products such as flavonoids and glycosides, by modulating circRNA-miRNA-mRNA networks, offer promising therapeutic strategies. The article also discusses the current technical challenges in circRNA research and its future application prospects in CRC, highlighting the need for further investigation into the role of circRNAs in tumor immune microenvironments and drug resistance mechanisms.